BEST PAPER AWARD - Andreou, Andreas S. (My University, 2026)
Recipient (with Michalis Pingos, PhD candidate) of the best paper award of the 17th International Conference on Software Engineering Advances (ICSEA) held in 2022 for our paper entitled “A Smart Manufacturing Data Lake Metadata Framework for Process Mining”
Keywords: Sciences